PKO Bank Polski as an institution of systemic importance for the development of the Polish economy - Włodarczyk, Bogdan (PKO Bank Polski jako instytucja o znaczeniu systemowym dla rozwoju polskiej ekonomii, 2014)
PKO Bank Polski is the biggest bank in the banking sector in Poland. It owns the major part of Polish banking capital. It dominates in financing households and enterprises of all sectors and participates in the biggest infrastructural projects. The condition and activity of PKO BP greatly influences the national economy, and therefore the economic growth. It is an important institution connected to the financial security of the real and financial spheres in Poland. The comparative analysis of the activity of PKO BP compared to its competitors showed the bank’s stable position but also the necessity of changes in order to keep the correct parameters of activity and its position as a leader in the Polish banking market
Nauki o Finansach = Financial Sciences, 2014, Nr 4 (21), s. 62-80
Keywords: banking sector; national economy; PKO Bank Polski; sektor bankowy; gospodarka narodowa